2019
DOI: 10.1111/apt.15162
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index in early pregnancy and future risk of severe liver disease: a population‐based cohort study

Abstract: Background:In young men, high body mass index (BMI) has been linked to liver disease later in life, but it is unclear if this also applies to women. Aim:To study the association between BMI early in life and development of liver disease later in life in women. Methods:We obtained data on early pregnancy BMI from 1 139 458 Swedish women between 1992 and 2015. National registers were used to ascertain incident severe liver disease, defined as cirrhosis, decompensated liver disease (hepatocellular carcinoma, oeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…A population‐based study of 1.2 million men showed that a high BMI during late adolescence was associated with an increased risk of severe liver disease later in life 7 (Table 1). Similar findings have been seen in young women 31 . One meta‐analysis reported a modest increase in the rate of developing severe liver disease (1.20) in people with obesity compared to those without this condition 24 (Table 1).…”
Section: Epidemiology Of Liver Disease In Obesitysupporting
confidence: 73%
See 1 more Smart Citation
“…A population‐based study of 1.2 million men showed that a high BMI during late adolescence was associated with an increased risk of severe liver disease later in life 7 (Table 1). Similar findings have been seen in young women 31 . One meta‐analysis reported a modest increase in the rate of developing severe liver disease (1.20) in people with obesity compared to those without this condition 24 (Table 1).…”
Section: Epidemiology Of Liver Disease In Obesitysupporting
confidence: 73%
“…Similar findings have been seen in young women. 31 One meta‐analysis reported a modest increase in the rate of developing severe liver disease (1.20) in people with obesity compared to those without this condition 24 (Table 1 ).…”
Section: Epidemiology Of Liver Disease In Obesitymentioning
confidence: 99%
“…With the increasing prevalence of overweight and obesity in the population, 1 including in pregnant women, 3 our results suggest that the future prevalence of NAFLD in the paediatric and adolescent populations will increase, most likely continuing into later life. It has previously been shown that a high BMI early in life is associated with development of severe liver disease, [30][31][32] and these results suggest that being exposed to obesity while at a reproductive age might also have cross-generational consequences. This further highlights the importance of obtaining a healthy lifestyle and a normal BMI prior to pregnancy, as part of family planning.…”
Section: Discussionmentioning
confidence: 81%
“…Studies were included from Europe (Sweden [21,22,[26][27][28]33,37,38], UK [20,32], Italy [20], Netherlands [20], and Spain [20]), North America (US [23,25,[29][30][31]34,[39][40][41] and Canada [36]), and Asia (Singapore [24] and China [35]), with data on over 24 million individuals. All the eligible studies were prospective or retrospective cohorts in design, and were all community-based general population cohorts, some defined by data linkage.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Nine of the studies of predominantly middleaged individuals included men and women in roughly equal numbers. Two studies looked at women only, with 1 of the cohorts recruiting women in the early stages of pregnancy only [28]. The 3 remaining studies recruited predominantly men-1 at army conscription (ages 18-20 years), producing a younger study population at baseline, with follow-up for nearly 40 years [26].…”
Section: Obesity and The Risk Of Incident Severe Liver Disease Eventsmentioning
confidence: 99%